« Sommes-nous donc issus du vide ? » : Oralité et quête de racines dans le documentaire finlandais contemporain - Aymeric Pantet (Mise au Point)
This article examines the use of the filmic essay by filmmakers from Finnish-Samic minorities as a means to revitalise, recover and disseminate their languages, cultures and roots. Two directors, Katja Gauriloff and Miia Tervo, have made two documentaries — Kaisa's Enchanted Forest (Kuun metsän Kaisa, 2016) and [Santra and the Talking Trees] (Santra ja puhuvat puut, 2013) — that affirm an identity and a cultural existence of languages that are threatened with extinction. Using a variety of types of images, the two films tell the stories of Kaisa, Gauriloff's Skolt grandmother, and Santra, the last Karelian bard. This article explores the search for language and identity, the question of intimacy with a minor ancestral language and the alternative narratives attached to it, as well as the legacy and renewal brought about by the transition from poem to film.